Optimization of gate location with integrated CAD/CAE system - Liu, Dongsheng. (2008)
The objective of the research described in this thesis is to develop a gate optimization routine for CAD/CAE integration for plastic injection molding. A constrained gate optimization routine, which is capable of optimizing the gate location without design constraints, is developed. The CAE technology used in this routine is MOLDFLOW.